Lietuvos chirurgų asociacijos suvažiavimas 2019 10 11–12 Klaipėda - Razbadauskas, Artūras (Lietuvos chirurgija, 2019)
Statement of purpose“Lietuvos chirurgija” (“Lithuanian Surgery”) is a peer-reviewed journal of the Association of Lithuanian Surgeons, the Lithuanian Association for Wound Care, the Lithuanian Association for Ambulatory Surgery,the Lithuanian Society of Endoscopists, the Lithuanian Society of Cardiothoracic Surgeons, the LithuanianSociety of Coloproctologists, the Lithuanian Society of Vascular Surgeons, the Lithuanian Society for MinimalInvasine Surgery, the Lithuanian Society of Neurosurgeons, the Lithuanian Society of Oncologists, the Lithuanian Society of Pathologists, the Lithuanian Society for Hand Surgery and Hand Rehabilitation, the Lithuanian Society of Traumatologists and Orthopedic Surgeons, the Lithuanian Society of Urologists,the Lithuanian Society of Paediatric Surgery, the Lithuanian Society of Maxillofacial Surgeons, the Lithuanian Society of Vertebrologists, Vilnius Surgical Society, Kaunas Region Surgical Society, Klaipėda Region SurgicalSociety, Šiauliai Region Surgical Society, Panevėžys Region Surgical Society.It has been designed to meet the needfor a rapid spreading of new and important information on the theory and practice of surgery and related sciences. The journal provides a rapid publication of original papers that contribute to knowledge in the fields of clinical surgery, experimental surgery and related sciences.The contributions are accepted in Lithuanian and English. The journal “Lietuvos chirurgija” is an officialperiodical (quarterly) scientific publication of the Lithuanian Republic. Selection of papers for publicationis based on the opinion of highly qualified reviewers who are supporters, consultants or members of the Editorial Board and the International Advisory Board.
Keywords: none